2013
DOI: 10.1093/infdis/jit817
|View full text |Cite
|
Sign up to set email alerts
|

IsdB-dependent Hemoglobin Binding Is Required for Acquisition of Heme by Staphylococcus aureus

Abstract: Staphylococcus aureus is a Gram-positive pathogen responsible for tremendous morbidity and mortality. As with most bacteria, S. aureus requires iron to cause disease, and it can acquire iron from host hemoglobin. The current model for staphylococcal hemoglobin-iron acquisition proposes that S. aureus binds hemoglobin through the surface-exposed hemoglobin receptor IsdB. IsdB removes heme from bound hemoglobin and transfers this cofactor to other proteins of the Isd system, which import and degrade heme to rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 48 publications
6
95
0
Order By: Relevance
“…We observed that HlgAB and LukED were each capable of promoting S. aureus growth (Figure 4C). To determine if this growth was dependent of hemoglobin acquisition, we used an isogenic strain lacking the S. aureus hemoglobin receptors IsdB and IsdH (Δ isdBH ) (Pishchany et al, 2014; Torres et al, 2006). In contrast to wild type (WT) S. aureus , the Δ isdBH strain was significantly growth impaired in medium supplemented with cell-free extracts from toxin treated erythrocytes (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that HlgAB and LukED were each capable of promoting S. aureus growth (Figure 4C). To determine if this growth was dependent of hemoglobin acquisition, we used an isogenic strain lacking the S. aureus hemoglobin receptors IsdB and IsdH (Δ isdBH ) (Pishchany et al, 2014; Torres et al, 2006). In contrast to wild type (WT) S. aureus , the Δ isdBH strain was significantly growth impaired in medium supplemented with cell-free extracts from toxin treated erythrocytes (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Should heme no longer be accessible as an iron source, we hypothesize that "active" SbnI would allow transcription of downstream sbn genes and that pre-formed L-Dap in the cell would allow for a rapid transition to SB-mediated iron uptake. The fine-tuning of SB and heme uptake systems in S. aureus is of interest because both sbn and isd genes have been implicated in virulence in S. aureus models of infection (16,25,26,(43)(44)(45)(46). …”
Section: Discussionmentioning
confidence: 99%
“…S. aureus binds free hemoglobin (at nanomolar concentrations in the blood) via the surface-exposed iron-regulated surface determinant (Isd) system. Heme is extracted, brought inside the cell, and degraded within the cytoplasm to access the iron (56). IsdB in particular is one member of the Isd family that binds hemoglobin.…”
Section: Discussionmentioning
confidence: 99%